The marketing analytics practitioner's guide volume 4 : retail and statistics - Charan, Ashok (Singapore : World Scientific Publishing Co. Pte. Ltd., 2024)
"As the use of analytics becomes increasingly important in today's business landscape, The Marketing Analytics Practitioner's Guide (MAPG) provides a thorough understanding of marketing management concepts and their practical applications, making it a valuable resource for professionals and students alike. The four-volume compendium of MAPG provides an in-depth look at marketing management concepts and their practical applications, equipping readers with the knowledge and skills needed to effectively inform daily marketing decisions and strategy development and implementation. It seamlessly blends the art and science of marketing, reflecting the discipline's evolution in the era of data analytics. Whether you're a seasoned marketer or new to the field, the MAPG is an essential guide for mastering the use of analytics in modern marketing practices. Volume IV is divided into two parts - Retail and Statistics for Marketing Analytics. Retail delves into the various aspects of retail tracking, sales and distribution, retail analytics, and category management. The chapter on retail tracking covers in detail the processes that make up a retail measurement service, including the metrics supported by the service, the key benefits of the service, and how the data is interpreted. The sales and distribution chapter covers five key managerial objectives - building distribution, targeting the right channels and chains, optimizing assortment, securing retailer support, and managing stocks in trade. The retail analytics chapter covers a range of diagnostic analytic tools used to extract insights from disaggregate outlet-level data. Category management offers a framework for retailers to manage their business and for suppliers to understand the dynamics of trade marketing. Statistics for Marketing Analytics covers basic statistics, sampling, and marketing mix modelling. It aims to equip readers with the statistical knowledge and tools necessary to analyse and interpret marketing data. The chapters in this part provide a comprehensive understanding of statistical methods and their applications in marketing analytics, including sampling techniques, probability distributions, hypothesis testing, and regression analysis"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Retail trade -- Management; Marketing -- Management